2005
DOI: 10.1111/j.1741-4520.2005.00080.x
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive epidemiology of anotia and microtia, Hawaii, 1986–2002

Abstract: The objective of this investigation was to describe the epidemiology of anotia and microtia with respect to various factors. The cases studied were all infants and fetuses with anotia or microtia identified by a population-based birth defects registry in Hawaii. The anotia and microtia rates were determined for selected factors and comparisons made among the subgroups by calculating the rate ratio (RR) and 95% confidence interval (CI). A total of 120 cases were identified, for a rate of 3.79 per 10,000 live bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
110
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(135 citation statements)
references
References 22 publications
22
110
3
Order By: Relevance
“…The mild male excess of cases with isolated ear CAs in the study was in agreement with the results of some previous studies [11,13,15,[18][19][20][21][22][23], though the cases with isolated microtia/anotia in the Italian registry did not show a male predominance [24]. The strong male excess in cases with unclassified multiple ear CA is worth mentioning, because in general previous studies did not have strict differentiation between cases with isolated and multiple ear CAs.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The mild male excess of cases with isolated ear CAs in the study was in agreement with the results of some previous studies [11,13,15,[18][19][20][21][22][23], though the cases with isolated microtia/anotia in the Italian registry did not show a male predominance [24]. The strong male excess in cases with unclassified multiple ear CA is worth mentioning, because in general previous studies did not have strict differentiation between cases with isolated and multiple ear CAs.…”
Section: Discussionsupporting
confidence: 82%
“…The obvious predominance of unilateral cases and among them a slight right side excess in cases with isolated microtia/anotia in our study corresponded to the previous observations in other studies/countries [11,13,15,[18][19][20][21][22][23][24][25].…”
Section: Discussionsupporting
confidence: 81%
“…With respect to the descriptive epidemiology of anotia and/or microtia, associations have been reported between anotia and/or microtia and high maternal age (Harris et al, 1996;Forrester and Merz, 2005), high maternal parity (Castilla and Orioli, 1986;Mastroiacovo et al, 1995;Harris et al, 1996;Forrester and Merz, 2005), race (Harris et al, 1996;Shaw et al, 2004;Forrester and Merz, 2005;Husain et al, 2008), sex (Harris et al, 1996;Sanchez et al, 1997;Shaw et al, 2004, Forrester andMerz, 2005), low maternal education (Shaw et al, 2004;Husain et al, 2008), prenatal drug exposure (Castilla and Orioli, 1986), advanced paternal age (Castilla and Orioli, 1986), low birth weight (Mastroiacovo et al, 1995;Forrester and Merz, 2005), gestational age (Forrester and Merz, 2005), and maternal diabetes (Mastroiacovo et al, 1995;Correa et al, 2008). Conflicting studies report significant or no significant association with maternal or paternal education (Castilla and Orioli, 1986;Mastroiacovo et al, 1995;Shaw et al, 2004), maternal acute or chronic illness (Castilla and Orioli, 1986), vaginal bleeding (Castilla and Orioli, 1986), residence at the time of delivery (Forrester andMerz, 2005, Husain et al, 2008), and gestational age (Castilla and Orioli, 1986).…”
Section: Introductionmentioning
confidence: 95%
“…There have been five other population-based descriptive studies of anotia/microtia, including in three U.S. states: California, Hawaii, and Texas (Mastroiacovo et al, 1995;Harris et al, 1996;Shaw et al, 2004;Forrester and Merz, 2005;Husain et al, 2008). From these five studies, anotia/microtia prevalence ranged from 0.76 per 10,000 births in France (Harris et al, 1996) to 2.77 per 10,000 live births in Texas (Husain et al, 2008), but on average 1.84 per 10,000 births (Harris et al, 1996).…”
Section: Introductionmentioning
confidence: 95%
“…There is a paucity of epidemiologic information about this condition, and most previous studies have been descriptive. These studies have revealed that risk factors for microtia include advanced maternal age [Harris et al, 1996;Forrester and Merz, 2005;Canfield et al, 2009], male sex [Harris et al, 1996;Shaw et al, 2004;Canfield et al, 2009], low maternal education [Shaw et al, 2004;Husain et al, 2008;Canfield et al, 2009], and Hispanic ethnicity [Harris et al, 1996;Shaw et al, 2004;Forrester and Merz, 2005;Husain et al, 2008;Canfield et al, 2009]. Proposed etiologies include hypoxia [Castilla et al, 1999], in utero exposure to thalidomide [Buyse, 1990;Carey, 1993], maternal influenza [Lopez-Camelo and Orioli, 1996], and maternal diabetes [Mastroiacovo et al, 1995;EwartToland et al, 2000;Correa et al, 2008].…”
Section: Introductionmentioning
confidence: 96%